Environment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
NGOs in ACP countries involved in environmental education or training programmes are invited to contact the European Environment Bureau before September 30, 1987 so that they may participate in projects implemented as part of the Loma Convantion...